Impact of statin therapy on the immature platelet count in patients with coronary artery disease: A single centre cohort study. (1st December 2018) - Verdoia, Monica; Nardin, Matteo; Negro, Federica; Rolla, Roberta; De Luca, Giuseppe; ,
Abstract: Background: Statins represent a pivotal therapy among patients with coronary artery disease (CAD), providing both lipid-lowering and pleiotropic, anti-thrombotic and anti-inflammatory benefits. Immature platelet count (IPC) has been proposed as the fraction of younger and potentially more reactive platelets, therefore potentially affecting the risk of major cardiovascular ischemic events. The aim of the present study was to evaluate the impact of statin therapy on IPC in patients with CAD. Methods: Patients undergoing coronary angiography in a single centre were included. IPC levels were measured by routine blood cells count (A Sysmex XE-2100) as the product of immature platelet fraction (IPF) and platelet count, in patients naïve or chronically treated with statins at admission. Results: We included in our study 642 patients, 61.2% treated with statins at admission. Patients on chronic statins were more often males, with a worse metabolic profile, but for lower total and LDL cholesterol, and a higher prevalence of major cardiovascular risk factors. The mean levels of IPC did not differ between statin treated and naive patients (7.9 ± 4.7 vs 7.7 ± 5, p  = 0.60) and neither the distribution of IPC across tertiles ( p  = 0.36). In fact, at multivariate regression analysis, statin use was not independently associated with the rate of IPC above the 3rd tertile (adjusted OR[95%CI] = 1.19[0.80–1.79], p  = 0.39). Moreover, among the 190 patients that introduced the therapy with statins at admission, the levels of IPC and major platelet parameters did not differ at a median follow-up of 32 days, as compared to chronically treated or non-treated patients. Conclusion: The present study shows that among patients with CAD the use of statins does not affect the immature platelet count or main platelet parameters. Highlights: Pleiotropic anti-platelet effects have been described with statins Immature platelet count (IPC) elevation has been proposed as marker of vascular damage and of the risk of cardiovascular ischemic events Statins could affect the IPC and therefore thrombotic risk, but such hypothesis has never been established Among 642 patients with CAD, we evaluated the impact of statin therapy at admission on the IPC We found that the use of statins does not affect the IPC or main platelet parameters